Testosterone and Androstenedione Blood Production Rates in Normal Women and Women with Idiopathic Hirsutism or Polycystic Ovaries - C. Wayne Bardin; Mortimer B. Lipsett (The Journal of Clinical Investigation, 1967)
The average plasma testosterone concentration of women with either hirsutism or polycystic ovaries and hirsutism was higher (p < 0.01) than that of normal women although the ranges overlapped. Testosterone blood production rates averaged 830 ± 120 SE and 1,180 ± 310 SE μg per day in the two groups of hirsute women and 230 ± 33 SE μg per day in normal women. The ranges did not overlap. The testosterone metabolic clearance rates of hirsute women (1,090 ± 140 SE L per day) and of men (1,240 ± 136 SE L per day) were significantly higher than those of normal women (590 ± 44 SE L per day). These differences persisted when the metabolic clearance rates were corrected for surface area. We suggest that testosterone metabolic clearance rates vary directly with some function of testosterone production. The mean plasma androstenedione levels (2.8 ± 0.35 SE and 2.8 ± 0.30 SE μg per L) and production rates (6,060 ± 450 SE and 7,360 ± 345 SE μg per day) of the women with hirsutism or polycystic ovaries, respectively, were significantly higher than those of normal women (1.5 ± 0.22 SE μg per L; 3,300 ± 830 SE μg per day). The androstenedione metabolic clearance rates were the same in each group. Plasma androstenedione was the precursor of 49% of plasma testosterone in normal women and of 26% of plasma testosterone in hirsute women. Thus, 74% of the plasma testosterone in these subjects must have been either secreted or derived from a precursor that did not enter the plasma androstenedione pool.